Differential diagnosis of uterine adenosarcoma: identification of JAZF1-BCORL1 rearrangement by comprehensive cancer genomic profiling - Chie Hasegawa; Kota Washimi; Yukihiko Hiroshima; Rika Kasajima; Keiji Kikuchi; Tsuguto Notomi; Hisamori Kato; Toru Hiruma; Shinya Sato; Yoichiro Okubo; Emi Yoshioka; Kyoko Ono; et al. (BMC, 2023)
Abstract Background Uterine adenosarcoma is a rare malignant tumor that accounts for 8% of all uterine sarcomas, and less than 0.2% of all uterine malignancies. However, it is frequently misdiagnosed in clinical examinations, including pathological diagnosis, and imaging studies owing to its rare and non-specific nature, which is further compounded by the lack of specific diagnostic markers. Case presentation We report a case of uterine adenosarcoma for which a comprehensive genomic profiling (CGP) test provided a chance to reach the proper diagnosis. The patient, a woman in her 60s with a history of uterine leiomyoma was diagnosed with an intra-abdominal mass post presentation with abdominal distention and loss of appetite. She was suspected to have gastrointestinal stromal tumor (GIST); the laparotomically excised mass was found to comprise uniform spindle-shaped cells that grew in bundles with a herringbone architecture, and occasional myxomatous stroma. Immunostaining revealed no specific findings, and the tumor was diagnosed as a spindle cell tumor/suspicious adult fibrosarcoma. The tumor relapsed during postoperative follow-up, and showed size reduction with chemotherapy, prior to regrowth. CGP was performed to identify a possible treatment, which resulted in detection of a JAZF1-BCORL1 rearrangement. Since the rearrangement has been reported in uterine sarcomas, we reevaluated specimens of the preceding uterine leiomyoma, which revealed the presence of adenosarcoma components in the corpus uteri. Furthermore, both the uterine adenosarcoma and intra-abdominal mass were partially positive for CD10 and BCOR staining. Conclusion These results led to the conclusive identification of the abdominal tumor as a metastasis of the uterine adenosarcoma. The JAZF1-BCORL1 rearrangement is predominantly associated with uterine stromal sarcomas; thus far, ours is the second report of the same in an adenosarcoma. Adenosarcomas are rare and difficult to diagnose, especially in atypical cases with scarce glandular epithelial components. Identification of rearrangements involving BCOR or BCORL1, will encourage BCOR staining analysis, thereby potentially resulting in better diagnostic outcomes. Given that platinum-based chemotherapy was proposed as the treatment choice for this patient post diagnosis with adenosarcoma, CGP also indirectly contributed to the designing of the best-suited treatment protocol.